Social Acceptance in Physical Education and the Regular Classroom: Perceived Motor Competency and Frequency and Type of Sports Participation - Anne G. M. de Bruijn; Femke van der Wilt (MDPI AG, 2023)
This study examined relations of primary school children's perceived physical competence and sports participation (frequency and type) with social acceptance in the regular classroom and physical education (PE) and whether these relations differed depending on the type of sport children participated in (team vs. individual sports). In total, 182 children (48.9% boys, mean age 9.90 years, SD = 1.23) filled out questions on their perceived physical competence and sports participation and indicated three peers with whom they liked/disliked working in PE and the regular classroom. Multilevel structural equation models in Mplus showed that frequency of sports participation was positively related to social acceptance in the context of PE. Additionally, for children in team sports, the frequency of sports participation was related to their social acceptance in PE, whereas for children in individual sports, perceived physical competence was related to social acceptance in PE. No relations were found in the regular classroom. Relations of perceived physical competence and sports participation with social acceptance seem to depend on the school context and the type of sport involved. In designing PE classrooms, children's physical competence and sports participation seem essential factors to take into account to provide all children with positive social experiences.